2022
DOI: 10.3390/cells11091455
|View full text |Cite
|
Sign up to set email alerts
|

In Silico, In Vitro, and Clinical Investigations of Cathepsin B and Stefin A mRNA Expression and a Correlation Analysis in Kidney Cancer

Abstract: The cysteine protease Cathepsin B (CtsB) plays a critical role in multiple signaling pathways, intracellular protein degradation, and processing. Endogenous inhibitors regulate its enzymatic activity, including stefins and other cystatins. Recent data proved that CtsB is implicated in tumor extracellular matrix remodeling, cell invasion, and metastasis: a misbalance between cathepsins and their natural inhibitors is often considered a sign of disease progression. In the present study, we investigated CtsB and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Glutaraldehyde has a known toxicity profile on living cells [ 41 ]; however, it exerts it mostly during the cross-linking reaction and therefore it was mitigated by extensive washing steps performed prior to cell administration. We chose two cancer cell lines investigated for lysosomal protease (cathepsin) expression: 769-P human renal cancer cells [ 42 ] and SKBR3 human breast cancer cells [ 10 ]. Both the cell lines were treated with ANP loaded with Rhodamine 123, and we measured the decrease of the dye fluorescence within 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutaraldehyde has a known toxicity profile on living cells [ 41 ]; however, it exerts it mostly during the cross-linking reaction and therefore it was mitigated by extensive washing steps performed prior to cell administration. We chose two cancer cell lines investigated for lysosomal protease (cathepsin) expression: 769-P human renal cancer cells [ 42 ] and SKBR3 human breast cancer cells [ 10 ]. Both the cell lines were treated with ANP loaded with Rhodamine 123, and we measured the decrease of the dye fluorescence within 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was reported that CtsB has a slight effect on mature albumin in comparison with other cystein cathepsins [ 46 ] and CtsD [ 47 ]. In this scenario, future investigations on the expression of more enzymes and their natural inhibitors [ 42 ] could shed light on the specific activity of different cathepsins in degrading ANPs. The major outcomes in this work are shown in Figure 7 .…”
Section: Discussionmentioning
confidence: 99%
“…A protein implicated in the prevention of the cytotoxic effects of many drugs is cathepsin B [ 47 ]. Increased expression of cathepsin B in RCC indicates its role in tumor progression [ 48 ]. Our results show that even if Cath B is expressed and active (except in ACHN cells) in RCC, nivolumab did not influence the expression or activity of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that low stefin A expression can promote the development of glioblastoma, breast cancer and head and neck cancer. However, CatB and stefin A can form a positive feedback loop during renal cell carcinoma progression in renal cell carcinoma [95]. Aberrant expression of stefin B is also associated with diseases.…”
Section: Decreased In Lysosomes and Increased In The Cytoplasmmentioning
confidence: 99%